STRATEGI KEPEMIMPINAN MANAGERIAL PAUD - SANTOSO, SOEGENG (PPs UNJ, 2011)
Managerial early childhood leadership strategy is an effort to coaching is aimed at children from birth to age six years conducted through the provision of educational stimulation to assist the growth and development physically and mentally so that children have a readiness in entering further education.Managerial early childhood leadership strategy has the function of instruction, consultative, exemplary, participatory, and delegation. From beberapi function can be used as an alternative in order to smooth the lead agency early childhood, growing, quality, socially acceptable and worthwhile in human life in the future.Keywords: strategy, leadership, managerial, early childhood